Thinking and Feeling, Ageing and Working - Choudhury, Sanjukta (2020)
Ageism, a significant ‘ism’ second only to racism and sexism, has been little studied in the diversity literature. Given older workers are staying on at work longer following abolishment of a mandatory retirement age in the UK, understanding what younger and older workers think of each other is a significant precursor to managing age diversity in workplaces and fostering cooperation between these two groups. This study qualitatively investigated perceptions and attitudes towards older employees among Millennials Knowledge Workers (born between 1980 and 2000) in UK workplaces by conducting semi-structured, one-to-one interviews and thematically analysing the data. It was found that Millennial knowledge workers generally view older workers positively in terms of their accumulated experiences, interpersonal skills, and their ability to remain calm and resilient during crises. Positive affective attitudes of admiration and respect were identified among Millennials who reported feeling guided and supported through informal mentorship roles. Negative perceptions included older workers being less adaptable to technology and change, and lacking creativity. Negative affective attitudes of insecurity and frustration were identified due to Millennials experiencing rejection and communication issues with older employees. Recommendations are made to address Millennials’ negative perceptions and harness positive ones with the aim of improving co-operation between co-workers belonging to an increasingly age-diverse workforce.